Anisotropic Printed Resistor with Linear Sensitivity Based on Nano–Microfiller‐Filled Polymer Composite (Adv. Electron. Mater. 11/2021). (10th November 2021) - Huang, Pei; Cao, Yingze; Wei, Yawen; Cheng, Xiang; Liu, Junfeng; Zhang, Shanshan; Wang, Pengfei; Chen, Shaosong; Xia, Zhidong
Abstract : Anisotropic Printed‐Resistor In article number 2100581, Pengfei Wang, Shaosong Chen, Zhidong Xia, and co‐workers systematically prepare and study an anisotropic printed‐resistor. 3D printing electronics provides great potential to build structural objects with multiple functionalities, with the assistance of shape design and the shear force on the filler orientation. Nano‐micro fillers filled anisotropic resistors are systematically explored on their printability, electromechanical behaviors, microstructure.